Profile of Dengue Hemorrhagic Fever Cases in Children - Fuadah, Novitasari Tsamrotul; Sarinengsih, Yuyun; Helena, Denni Fransiska (Journal of Language and Health, 2024)
Cases of Dengue Hemorrhagic Fever (DHF) in Bandung have increased in 2024. DHF is caused by the Dengue virus, which is transmitted through the bite of the Aedes aegypti mosquito. It can affect all age groups but primarily affects children, with one of its clinical manifestations being a decrease in platelet levels. DHF with clinical manifestations of shock in pediatric patients carries a risk of death if not treated promptly and appropriately. This study aims to determine the profile of DHF cases in children at the Ibrahim Adjie Health Center in Bandung, including the children's age, gender, education level, platelet count, and hematocrit levels.This study employed a descriptive retrospective method. The population in this study consisted of children aged ≤ 18 years diagnosed with DHF who sought treatment at the Ibrahim Adjie Health Center in Bandung City from January to October 2024, totaling 129 children. A sample of 54 children was obtained using purposive sampling. Data collection utilized secondary data extracted from patient medical records. Univariate data analysis was presented in frequency distribution tables. The study results showed that children with DHF were distributed as follows: 9 children (17%) aged 1–3 years, 7 children (13%) aged >3 to <6 years, 31 children (57%) aged 6–12 years, 7 children (13%) aged >12–18 years, and none under 1 year old. Male children accounted for 29 cases (54%) and females for 25 cases (46%). Based on education level, 23 children (43%) had not yet started school, 24 children (44%) were in elementary school, 5 children (9%) were in junior high school, and 2 children (4%) were in senior high school. All 54 children (100%) had low platelet counts, defined as <150,000/µL of blood. Hematocrit levels varied: 4 children (7%) had low hematocrit levels, 41 children (76%) had normal levels, and 9 children (17%) had high levels. It can be concluded that most children with DHF are aged 6–12 years, or school-aged. There is no significant difference between male and female cases. The majority occur at the elementary school education level. All children experienced thrombocytopenia or a decrease in platelet count, and most had normal hematocrit levels.